Interpretation of Surat Al-Qasas from verse (1-18) By the scholar Muin al-Din al-Iji (d. 905 AH) - study and investigation (Journal of the College of Basic Education, 2022)
Manuscripts are part of the nation’s heritage, and an important document of its civilized and national existence. Therefore, nations sought to preserve their manuscripts, and to master the means of this maintenance, as it was the first blazing flame of forensic sciences, and with it begins codification.Manuscripts are of very great importance, because the nation’s knowledge and jurisprudence are recorded in them, as the revelation and its interpretation, the hadiths of the Prophet, peace and blessings of God be upon him and his family and their explanations, the science of the imams, their history, their language, and other things that are related to them were written down.And since this heritage is a part of human knowledge that generations have to pass on safely to those after them, in addition to being a part of our history that we are proud of; Scholars in general, and we, the sons of this nation in particular, have to rise to its revival and verify its manuscripts, and among those valuable manuscripts in interpretation: (Jami` al-Tibyan fi tafsir al-Qur’an), which is one of the treasures of the ancient Islamic heritage, because it contains a statement of the Book of God Almighty, and an explanation of its meanings. , and a statement of its vocabulary, and clarification of its implications.